Observations key to understanding solar cycles: a review - Martin, Sara F. (Frontiers in Astronomy and Space Sciences, 2024)
A paradigm shift is taking place in the conception of solar cycles. In the previous conception, the changing numbers of sunspots over intervals of 9 to 14 years have been regarded as the fundamental solar cycle although two average 11-year cycles were necessary to account for the complete magnetic cycle. In the revised picture, sunspots are a phase in the middle of two 22-year overlapping solar cycles that operate continuously with clock-like precision. More than twenty researchers contributed to the initial research papers from 2014 through 2021 which are dramatically altering the perception of solar cycles. The two 22-year cycles overlap in time by 11 years. This overlap is coincidentally the same average duration as the sunspot phase in each 22-year cycle. This coincidence and the relative lack of knowledge of the large numbers of small active regions without sunspots, is what led to the previous paradigm in which the 11-year sunspot phases were misinterpreted as a single fundamental solar cycle. The combination of the two 22-year solar cycles, with their large numbers of short-lived active regions and ephemeral active regions are now understood to be the fundamental cycle with the proposed name "The Hale Solar Cycle." The two 22-year solar cycles each occupy separate but adjacent bands in latitude. The orientations of the majority of bipolar magnetic regions in the two adjacent bands differ from each other by ~180 degrees. Both bands continuously drift from higher to lower latitudes as has been known for sunspot cycles. However, the polarity reversal occurs at the start of each 22-year cycle and at higher latitudes than for sunspots. This paradigm shift in the concept of solar cycles is resulting in major reconsiderations of additional topics on solar cycles in this review. These are: (1) the large role of ephemeral active regions in the origin of solar cycles, (2) the depth of the origin of active regions and sunspots, (3) the mechanisms of how areas of unipolar magnetic network migrate to the solar poles every 11 years, and (4) the nature of the polarity reversal in alternate 22year cycles rather than 11-year cycles.